2022
DOI: 10.3389/feart.2022.835142
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Joint Impact of Climatic Variables on Meteorological Drought Using Machine Learning

Abstract: With the intensification of climate change, the coupling effect between climate variables plays an important role in meteorological drought identification. However, little is known about the contribution of climate variables to drought development. This study constructed four scenarios using the random forest model during 1981–2016 in the Luanhe River Basin (LRB) and quantitatively revealed the contribution of climate variables (precipitation; temperature; wind speed; solar radiation; relative humidity; and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The responsiveness of SPEI to fluctuations in evaporation demand, as well as its multiscale properties, has made it a widely utilized tool in contemporary drought research [17,18]. Nevertheless, research has demonstrated that the impact of evaporation demand on SPEI is considerably smaller compared to precipitation among the climate variables influencing SPEI [19]. Following that, Hobbins et al introduced EDDI, which exclusively relies on evaporation demand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The responsiveness of SPEI to fluctuations in evaporation demand, as well as its multiscale properties, has made it a widely utilized tool in contemporary drought research [17,18]. Nevertheless, research has demonstrated that the impact of evaporation demand on SPEI is considerably smaller compared to precipitation among the climate variables influencing SPEI [19]. Following that, Hobbins et al introduced EDDI, which exclusively relies on evaporation demand.…”
Section: Introductionmentioning
confidence: 99%
“…EDDI is a drought index with a physical basis, encompassing multiple scales and displaying efficient capability in identifying both abrupt and prolonged droughts [12,20]. In comparison to SPEI and SPI, EDDI demonstrates a higher capacity to capture drought events of greater intensity and longer duration [19]. It also serves as a valuable tool for early warning for agricultural drought, hydrological drought, and fire weather risks.…”
Section: Introductionmentioning
confidence: 99%
“…Standardized drought indices are widely used to evaluate drought properties such as frequency, intensity and duration [16][17][18]. Numerous drought indices have been developed to quantify drought characteristics.…”
Section: Introductionmentioning
confidence: 99%